Pengaruh Persepsi Kemudahan Penggunaan, Persepsi Keamanan Dan Manfaat Terhadap Minat Pemakaian Financial Technology Pada Penggunaan Pembayaran Digital UMKM Kabupaten Badung - Darmayanti, Rai; Ayu, Putu Cita; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2025)
Fintech is the use of technology to provide innovative solutions in the financial industry. Fintech combines elements of finance with information and communication technology. The goal is to create products and services that are more efficient, fast and easily accessible. This study aims to examine the Influence of Perceived Ease of Use, Perceived Security and Benefits on Interest in Using Financial Technology on the Use of Digital Payments for MSMEs in Badung Regency. This study uses a quantitative approach by determining the sample using the Slovin formula with an error rate of 10%, resulting in a total of 100 respondents in MSMEs in Badung Regency and data was collected through questionnaires. The data used are primary data in the form of responses from respondents, and processed using SPSS. The results of this study indicate that Perceived Ease of Use (X1), Perceived Security (X2), and Benefits (X3) have a positive and significant effect on Interest in Using Financial Technology (Y) in Badung Regency.